Combinatorial Methods for Improving Lithium Metal Cycling Efficiency. Issue 13 (1st January 2018) - Genovese, Matthew; Louli, A. J.; Weber, Rochelle; Sanderson, R. J.; Johnson, M. B.; Dahn, J. R.
Abstract : An efficient combinatorial approach for the design and evaluation of surface coatings to improve lithium metal cycling efficiency is demonstrated. The reliability of a 64 electrode combinatorial cell was verified through lithium metal cycling in a range of electrolytes on unmodified Ni and Cu electrode plates with parallel verification using conventional Cu|| Li coin cells. A 1M LiPF6 FEC:TFEC fluorinated electrolyte demonstrated the best performance with coulombic efficiencies of 98.3% and 97.6% in the combinatorial cell (cyclic voltammetry) and coin cell (galvanostatic cycling) respectively, compared to only 91.0% (CV) and 90.3% (galvanostatic) for a 1M LiPF6 EC:DEC control electrolyte. High throughput sputtering was used to deposit different thin film coatings of varying thickness on the 64-channel cell plates to probe the lithium cycling performance as a function of electrolyte and surface coating. Zn surface coatings with thickness between 400–900 nm proved most beneficial; significantly reducing the lithium nucleation potential and leading to more stable cycling at high coulombic efficiency (99.0% in the combinatorial cell with FEC:TFEC electrolyte). These findings not only highlight some useful strategies for improving lithium metal cycling efficiency, but also show the potential for more advanced combinatorial analysis to design superior anodes for lithium metal cells.